Dosing of Antimycotic Treatment in Sepsis–Induced Liver Dysfunction by Functional Liver Testing with LiMAx® - Carmen Kirchner; Jasmin Sibai; Elke Schwier; Dietrich Henzler; Claas Eickmeyer; Günther Winde; Thomas Köhler (Case Reports in Critical Care)
Background. Sepsis-treatment is one of the major challenges in our time. Especially fungal infections play an important role in patient’s morbidity and mortality. In patients with septic shock, liver function is often significantly impaired and therefore also hepatic drug metabolism is altered. Case Presentation. We report about a 56-year-old man suffering from invasive fungal infection with multiorgan failure, after complicated medical history due to symptomatic infrarenal aortic aneurysm. On the first postoperative day, a CT scan was undertaken due to massive back pain showing renal infarction on both sides. As qualitative and quantitative renal function was impaired, hemodialysis was started immediately. Subsequently, the patient developed a compartment syndrome of the left leg and underwent fasciotomy. On admission day 7, the patient presented with hematochezia leading to colonoscopy. During this procedure, an ischemic colitis was observed. As conservative treatment failed, the patient underwent Hartmann’s procedure due to progredient ischemia followed by a worsening of the clinical status due to sepsis. The patient suffered from an invasive fungal infection with Candida spp. and Aspergillus spp. Systemic antifungal treatment was initiated. Although azoles are considered first-line treatment in these cases we chose the echinocandin caspofungin for its presumed lower impact on liver function compared to azoles like voriconazole or Amphothericin B. However, caspofungin is also metabolised in the liver and can cause hepatotoxic effects. Therefore we measured metabolic liver function capacity using LiMAx®and adapted the patient’s dose of caspofungin to the evaluated liver function capacity to achieve an effective and liver-protective level of the active drug. After complicated medical history with 15 weeks of hospital stay, the patient was discharged in general good condition. Conclusions. To our knowledge, this is the first report that relates antimycotic drug dosing to a functional liver test. We provide a new approach for sepsis treatment considering liver function capacity to optimize dosage of hepatically metabolised drugs with potential hepatotoxic effects.